Estudo, caracterização e avaliação de resíduos de caldeira na purificação de biodiesel metílico de soja e óleo residual de fritura de soja - Akel, Ralhid (2020)
The quality of biodiesel before being mixed with petroleum diesel is related to its purification process, in order to remove the present contaminants. The production of biodiesel can be made from vegetable oils, where the most common is soybean oil, as well as animal fat. The use of residual frying oil (RFO) may be an alternative, provided the cost of purifying this material is interesting. Currently, there are two types of biodiesel purification, dry and wet, the dry method being the alternative chosen to be evaluated in this work. In order to carry out the study of the appropriate adsorbent for biodiesel purification, boiler residues, a mixture of rice husk and eucalyptus husk, were evaluated. These boiler residues were collected and treated with HCl, to be adjusted to the pH (1, 3, 5 and 7). The boiler residues were tested in the purification process of methyl soybean biodiesel (MSB), and also with RFO samples, in order to evaluate their purification efficiency. The boiler residues tested were promising, with only 5g representing about 12% mixed in 40mL in the RFO or MSB, they were able to adsorb substances such as moisture and organic materials, proven and characterized through the techniques TG DTA, TG-DSC coupled to FTIR, infrared spectroscopy, X-ray fluorescence (EDX) and emission spectrometry by ICP-OES. It was observed that the boiler waste, presented as the best result in the acidity index for both the MSB and the RFO, it was the RST that obtained a reduction of 61% and remaining within the acceptable limits. EDX tests show a large amount of silica, about 51% in the RT1 sample. Regarding the humidity test, since they did not reach the values established according to ANP resolution 045/2014, it was observed that the samples had decreases in their indexes, as in samples RT1 for MSB and RST for RFO, which reduced about 38% of its values. The results of the 1H NMR showed that there were no changes in its characteristics such as the ester content, which remained close to its percentages.